Analysis of Opportunities and Challenges of Halal Product Certification for MSMEs in Sidoarjo Regency: Analisis Peluang dan Tantangan Sertifikasi Produk Halal bagi UMKM di Kabupaten Sidoarjo - Anggrayni, Bilqis Sabrina (Journal of Halal Lifestyle and Sustainability, 2025)
This study aims to analyze the opportunities and challenges faced by Micro, Small and Medium Enterprises (MSMEs) actors in the halal product certification process in Sidoarjo Regency. Halal certification is an important instrument in ensuring the halalness and safety of products, especially in the food and beverage sector, which is mostly consumed by the Muslim community. This research uses a descriptive qualitative approach with data collection techniques in the form of semi-structured interviews, field observations, and documentation studies. The main informants consist of MSME players, representatives of the Cooperative and SME Office, and related institutions such as MUI/LPPOM. The results show that the main opportunities for halal certification for MSMEs lie in increasing product competitiveness, wider market access, and policy support from local governments. However, the certification process still faces various challenges, such as lack of understanding of procedures, financial limitations, lack of human resources, and limited access to information and assistance. In addition, not all businesses are able to trace the halalness of raw materials thoroughly. This study recommends strengthening the synergy between the government, certification bodies, and businesses through integrated facilitation programs, simplifying procedures, and increasing halal literacy. Inclusive and efficient halal certification is expected to encourage the growth of competitive and sustainable MSMEs.